2008
DOI: 10.1099/mic.0.2008/020941-0
|View full text |Cite
|
Sign up to set email alerts
|

Host α-adducin is redistributed and localized to the inclusion membrane in Chlamydia- and Chlamydophila-infected cells

Abstract: A large-scale analysis of proteins involved in host-cell signalling pathways was performed using chlamydia-infected murine cells in order to identify host proteins that are differentially activated or localized following infection. Two proteins whose distribution was altered in Chlamydia trachomatis-infected cells relative to mock-infected cells were the actin-binding protein adducin and the regulatory kinase Raf-1. Immunoblot analysis with antibodies to both phosphorylated and non-phosphorylated forms of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…143 Recent studies from our group also revealed that in epithelia a-adducin down-regulation results in loss of junctional assembly and reduced barrier integrity, 144 whereas in endothelial cells, severe disruption of VE-cadherinbased AJs was detected. 145 Similar to other studies where application of proapoptotic agents, cytokines or invading bacteria resulted in rapid removal of adducin from intercellular junctions, [146][147][148] we demonstrated a loss of adducin from endothelial junctions under treatment with inflammatory mediators such as lipopolysaccharide (LPS), TNF-a and thrombin. 145 However, how exactly adducin controls endothelial barrier integrity is not clear yet.…”
Section: Permeability Regulation By Abpssupporting
confidence: 85%
“…143 Recent studies from our group also revealed that in epithelia a-adducin down-regulation results in loss of junctional assembly and reduced barrier integrity, 144 whereas in endothelial cells, severe disruption of VE-cadherinbased AJs was detected. 145 Similar to other studies where application of proapoptotic agents, cytokines or invading bacteria resulted in rapid removal of adducin from intercellular junctions, [146][147][148] we demonstrated a loss of adducin from endothelial junctions under treatment with inflammatory mediators such as lipopolysaccharide (LPS), TNF-a and thrombin. 145 However, how exactly adducin controls endothelial barrier integrity is not clear yet.…”
Section: Permeability Regulation By Abpssupporting
confidence: 85%
“…The membrane skeletal protein γ-adducin is localized at spectrin-actin junctions; it binds calmodulin and is an in vivo substrate for protein kinase C (PKC) and Rho-associated kinases. It regulates the remodeling of AJs in human epithelial cells and has been reported to be redistributed during bacterial infections ( 40 ). The downregulation of γ-adducin in our model of the bronchial epithelium gives intriguing insights into a potential role of this protein in the loss of stabilization of epithelial junctions during respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…This novel function of adducins could be important for remodeling of epithelial junctions during embryonic morphogenesis, a steady-state rejuvenation of epithelial layers, and restoration of epithelial barrier during wound healing. Furthermore, given the fact that adducins can be rapidly removed from intercellular junctions and degraded by cytokines (Pariser et al , 2005), invading bacteria (Chu et al , 2008), and proapoptotic agents (van de Water et al , 2000), adducins dysfunctions could mediate disruption of epithelial barriers during infection and inflammation. Further studies are required to test the roles of these membrane skeleton proteins in mucosal diseases.…”
Section: Discussionmentioning
confidence: 99%